ISTILAH KEKERABATAN DALAM BAHASA INGGRIS DAN BAHASA TOBELO (SUATU ANALISIS KONTRASTIF) - JANGOLOH, SALAM D.; KODONG, FENTJE; PAMANTUNG, RINA P. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACT This research attempts to analyse and to describe kinship terms of English and Tobelo language. English and Tobelo languages have specific patterns of kinship terminologies. Both of them have a special and unique set of terms to indicate their kinship terminologies.This research aims to make a contrastive analysis between kinship of English and Tobelo languages, and finding out their similarities and differences. The method of research is qualitative through the descriptive as the approach. This research uses the theories of Lado as well as descriptive method by Burling (1971) and also Lounsburry in Leech to find out the similarities and differences of kinship terms between English and Tobelo languages. The English data were collated from several relevant text books and same sources from internet and previous thesis about the term of kinship that has been done before, Whereas the Tobelo language data collected from informant through investigation.The result of this research shows that English and Tobelo languages have similarities in terms of sex, generation, lineage and age. Their also have differences like the English terms of kinship do not separate the age of relative, while Tobelo language does. In terms of generation, the Engglish and Tobelo have the same generation such as four generations above and below ego.Key words:Kinship term in English and Tobelo languages Analysis Contrastive.